2015
DOI: 10.1111/jopr.12395
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes Based on Patients’ Self‐Reported Measures after Receiving New Clasp or Precision Attachment‐Retained Removable Partial Dentures

Abstract: Treatment outcomes were better in the PA-RPD group than the C-RPDs. Women showed greater concern for the treatment outcomes; their rates were significantly better than in male patients in the PA-RPD group; however, when their satisfaction was lower, their rates were significantly worse than in male patients (in the C-RPD group).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…However, subgroup analysis of studies that provided clasp‐retained RPDPs revealed better OHRQOL in patients with SDA than in patients with clasp‐retained RPDPs. In one of the RCTs, patients with precision attachment‐retained RPDPs exhibited significantly better OHRQoL than those with clasp‐retained RPDPs , which suggests that precision attachment dentures, which lack metal clasps, provide better aesthetics and OHRQoL than clasp‐retained RPDPs. Third, the meta‐analysis only included data gathered over as short a follow‐up period as 12 months, because only one study had presented longer follow‐up data.…”
Section: Discussionmentioning
confidence: 99%
“…However, subgroup analysis of studies that provided clasp‐retained RPDPs revealed better OHRQOL in patients with SDA than in patients with clasp‐retained RPDPs. In one of the RCTs, patients with precision attachment‐retained RPDPs exhibited significantly better OHRQoL than those with clasp‐retained RPDPs , which suggests that precision attachment dentures, which lack metal clasps, provide better aesthetics and OHRQoL than clasp‐retained RPDPs. Third, the meta‐analysis only included data gathered over as short a follow‐up period as 12 months, because only one study had presented longer follow‐up data.…”
Section: Discussionmentioning
confidence: 99%
“…They provide retention without the need for clasp retainers, thereby enhancing denture esthetics [7][8][9] . Resilient extracoronal attachments have been indicated for distal extension base cases to prevent torque of abutments and to distribute load favorably between abutments and the edentulous ridge [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Persic S. et al [13] concluded that the PA-RPD showed superior OHRQoL than C-RPD on the other hand Montero et. al.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%